Synthesis and applications of polyoxometalates - Pang, Xi Ya (Nanyang Technological University, 2020)
The application of POMs as a source of catalyst together with TiO2 in overcoming the wastewater environmental pollution. As the adjustable structure and stable properties of POMs made them to be ideal for dye degradation. This experiment investigates the potential of POMs to be attached to TiO2 may led to higher performance for wastewater treatment. As POMs is found to be soluble in water and some organic solvents. Hence by attaching POMs to TiO2 could enhance future use. The wastewater degradation in this experiment will mainly focus on methylene blue. First by preparing the methylene blue solution and adding the catalyst in the solution. 50% intensity of UV light will be shined on sample and each sample will be taken in 5 min intervals for 5 times. By changing different variables in synthesising of POMs may affect the crystal structure and time taken for formation of POMs.